Pengaruh Kesejahteraan Karyawan terhadap Kinerja Karyawan PT Citra Mahkota di Kecamatan Ella Hilir Kabupaten Melawi - Erwin (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2022)
The welfare of the community is significant to create the distinguished human resources and able to compete in the world of work, as well as to keep up with the times, where human resources are required to be able to work in their respective fields. The employee’s welfare is also fundamental because the employees are the driving force for the corporation. By fulfilling of the employee’s rights, the morale in workplace will increase automatically, along with the output. Therefore, this study aims to investigate the effect of the employee’s welfare towards his/her working performance at PT Citra Mahkota in Ella Hilir District, Melawi Regency, West Kalimantan Province. The employee’s performance is the achievement given by the employees to the corporation, either in the form of accomplishments or results. From the research conducted, the results show that the employee’s welfare affects their working performance. The results of this research show that 36% of economic welfare affects the employee’s performance of PT Citra Mahkota.